Answer:
[tex]26[/tex]
Step-by-step explanation:
We have:
[tex]\sqrt{13}\times\sqrt{52}[/tex]
Notice that 52 is the product of 13 and 4. So:
[tex]=\sqrt{13}\times \sqrt{13\times 4}[/tex]
We can separate the second one:
[tex]=\sqrt{13}\times\sqrt{13}\times\sqrt{4}[/tex]
We can combine the first two:
[tex]=\sqrt{13\times13}\times\sqrt4[/tex]
We can write [tex]13\times13[/tex] as [tex]13^2[/tex]. So:
[tex]=\sqrt{13^2} \times \sqrt4[/tex]
The square root and the square will cancel. The square root of 4 is 2. So:
[tex]=13\times2[/tex]
Multiply:
[tex]=26[/tex]
Therefore:
[tex]\sqrt{13}\times\sqrt{52}=26[/tex]